Factors Associated with Review Board Dispositions following Re‐hospitalization among Discharged Persons found Not Criminally Responsible. (4th April 2016) - Wilson, Catherine M.; Nicholls, Tonia L.; Charette, Yanick; Seto, Michael C.; Crocker, Anne G.
Abstract: In the Canadian forensic mental health system, a person found Not Criminally Responsible on account of Mental Disorder (NCRMD) and given a conditional discharge returns to the community while remaining under the jurisdiction of a provincial/territorial Review Board. However, the individual can be re‐hospitalized while on conditional discharge, for reasons such as substance use, violation of conditions, or violence. We investigated whether being re‐hospitalized has an impact on the factors associated with the subsequent Review Board disposition. Persons found NCRMD from the three largest Canadian provinces who were conditionally discharged at least once during the observation period were included in the sample ( N = 1, 367). These individuals were involved in 2, 920 disposition hearings; nearly one‐third of patients (30%) were re‐hospitalized after having been conditionally discharged by the Review Board. The factors examined included the scales of the Historical Clinical Risk Management‐20 and salient behavior that occurred since the previous hearing, such as substance use or violence. The greater presence of clinical items resulted in a greater likelihood of a hospital detention decision at the next hearing. The effect was larger for the re‐hospitalized group than for the group who successfully remained in the community since the last hearing. The results suggest that dynamic factors, specifically indicators of mental health, are heavily weighted by the Review Boards, consistent with the literature on imminent risk and in line with the NCRMD legislation. Copyright © 2016 John Wiley & Sons, Ltd.